Respostas

2014-08-30T22:46:47-03:00
A)   5!3!    =  1 / 24
   4.3! 6.5!

b) n(n-1)(n-2)! = n(n-1) = n² - n
     (n-2)!
  • Usuário do Brainly
2014-08-30T23:06:01-03:00
Olá, Gustavinho !

a) \dfrac{3!\cdot5!}{4!\cdot6!}

Observe que, 4!=4\times3! e 6!=6\times5!. Assim:

\dfrac{3!\cdot5!}{4!\cdot6!}=\dfrac{3!\cdot5!}{4\times3!\cdot6\times5!}=\dfrac{1}{4\times6}=\dfrac{1}{24}.

b) \dfrac{n!}{(n-2)!}

Note que, n!=n(n-1)!=n(n-1)(n-2)!, logo:

\dfrac{n!}{(n-2)!}=\dfrac{n(n-1)(n-2)!}{(n-2)!}=n(n-1)

Espero ter ajudado, até mais ^^